Burkina Faso : Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria and Augmentation of Access: Staff Report; Debt Sustainability Analysis; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burkina Faso. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper presents findings of the Fourth Review Under the Extended Credit Facility Arrangement for Burkina Faso. Near-term policy discussions focused on specifying 2012 financing needs arising from the shocks to help prevent crowding out the authorities' development program-Strategy for Accelerated Growth and Sustainable Development. The authorities have implemented decisive adjustment measures, without which financing needs would be much higher. Program performance was strong in 2011, despite domestic social unrest and political turmoil in neighboring Cote d'Ivoire. All quantitative performance criteria and all indicative targets were met.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet